2014
DOI: 10.1589/jpts.26.1949
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Robot-assisted Gait Training Combined with Functional Electrical Stimulation on Recovery of Locomotor Mobility in Chronic Stroke Patients: A Randomized Controlled Trial

Abstract: [Purpose] The purpose of the present study was to investigate the effects of robot-assisted gait training combined with functional electrical stimulation on locomotor recovery in patients with chronic stroke. [Subjects] The 20 subjects were randomly assigned into either an experimental group (n = 10) that received a combination of robot-assisted gait training and functional electrical stimulation on the ankle dorsiflexor of the affected side or a control group (n = 10) that received robot-assisted gait trainin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
50
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(50 citation statements)
references
References 23 publications
0
50
0
Order By: Relevance
“…Advanced technology is increasingly being applied in everyday clinical practice, specifically in neurorehabilitation. Lately, multimodal approaches, for example, combinations of brain stimulation [4] or functional electrical stimulation [5] and robotic gait training, have shown promising results. However, when treating a patient with the help of advanced technology, it is crucial that clinicians still make decisions based on their knowledge of motor learning principles [6], biomechanics, neurophysiology, and neuroplasticity [7], and, in the case of lower extremity rehabilitation, their knowledge of locomotor training principles [8] and gait therapy in general.…”
Section: Introductionmentioning
confidence: 99%
“…Advanced technology is increasingly being applied in everyday clinical practice, specifically in neurorehabilitation. Lately, multimodal approaches, for example, combinations of brain stimulation [4] or functional electrical stimulation [5] and robotic gait training, have shown promising results. However, when treating a patient with the help of advanced technology, it is crucial that clinicians still make decisions based on their knowledge of motor learning principles [6], biomechanics, neurophysiology, and neuroplasticity [7], and, in the case of lower extremity rehabilitation, their knowledge of locomotor training principles [8] and gait therapy in general.…”
Section: Introductionmentioning
confidence: 99%
“…When FES was only applied to the dorsiflexor muscle during the swing phase of gait, the peak maximum dorsiflexion angle increased by approximately 6.0°, and the peak knee flexion angle barely changed 16 ) . The maximum knee flexion angle was also shown to be significantly increased by 18° when FES was applied to the affected dorsiflexors of patients walking with robot-assisted gait training 9 ) .…”
Section: Discussionmentioning
confidence: 99%
“…It has been proven that real-time control plays a key role in the success of FES. Several previous studies demonstrated that FES significantly increased the step length of affected limbs 7 , 8 , 9 ) , dorsiflexion at initial contact during walking 10 ) , maximal knee flexion 9 ) , and EMG activities of muscles related to hemiplegic gait 11 ) .…”
Section: Introductionmentioning
confidence: 95%
“…These devices have alleviated the physical workload for the therapists and have thus gained popularity. Several studies have also suggested that gait-training robots can improve locomotor recovery in stroke patients 12 ) .…”
Section: Introductionmentioning
confidence: 99%